PENGARUH SELEKSI TERHADAP PEROLEHAN GENETIK PADA UJI KETURUNAN GENERASI PERTAMA (F-1) JABON MERAH (Anthocephalus macrophyllus (Roxb.) Havil) DI WONOGIRI - Surip Surip; Sapto Indrioko; Arif Nirsatmanto; Teguh Setyaji (Jurnal Pemuliaan Tanaman Hutan, 2017)
Selection is a fundamental process in the establishment of a progeny trial that will be converted into a seedling seed orchard. In present study, selection practiced in first-generation progeny trial of jabon merah (Anthocephalus macrophyllus Roxb. Havil.) was observed. The study was aimed to find out a criteria selection accompanied with the effective coefficient weight for predicting genetic gain in the first-generation progeny trial of jabon merah. The trial was established in Wonogiri which was laid out in randomized complete block design (RCBD) using 55 families, 4 replications, 4 tree-plot with a spacing of 4 x 2 meter. Measurement was conducted at 40 months after planting covering tree height, diameter at breast height, stem straightness, stem volume. First within-plot selection by culling 2 poorer trees within each plot was practiced at 46 months age. Selection differential from within-plot selection was used to derive coefficient weight which was then applied to predict genetic gain. Results of study showed that selection differential from first within-plot selection were positive for all measured traits. Stem volume was observed as highest priority trait with coefficient weight for each trait were -0.0863 (height), 0.1426 (diameter), 0.2195 (stem straightness), 2.3025 (stem volume). Prediction of genetic gain from within-plot selection were 3,50% (height), 3.58% (diamater), 3.41% (stem straightness), 7.40% (stem volume). While the gain from family selection were 2.80%, 3.75%, 3.54%, 7.10% for height, diamater, stem straightness, stem volume, respectively.